2019
DOI: 10.1002/1873-3468.13688
|View full text |Cite
|
Sign up to set email alerts
|

Protein structure determination using a Riemannian approach

Abstract: Protein NMR structure determination is one of the most extensively studied problems. Here, we adopt a novel method based on a matrix completion technique – the Riemannian approach – to rebuild the protein structure from the nuclear Overhauser effect distance restraints and the dihedral angle restraints. In comparison with the cyana method, the results generated via the Riemannian approach are more similar to the standard X‐ray crystallographic structures as a result of the simple but powerful internal calculat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 138 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…For instance, Boyd et al provided evidence of [4Fe–4S] cluster transfer from S . Typhimurium holo-ApbC to S. cerevisiae apo-isopropylmalate isolomerase (Leu1) 35 ; likewise, Zhao et al recently showed transfer of [4Fe-4S] clusters between M. maripaludis holo-MMP0704 and E. coli apo-aconitase proteins 38 . A survey of 100 sequenced H. pylori genomes showed that the ApbC sequence is highly conserved in H. pylori (98.37–100% identity).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, Boyd et al provided evidence of [4Fe–4S] cluster transfer from S . Typhimurium holo-ApbC to S. cerevisiae apo-isopropylmalate isolomerase (Leu1) 35 ; likewise, Zhao et al recently showed transfer of [4Fe-4S] clusters between M. maripaludis holo-MMP0704 and E. coli apo-aconitase proteins 38 . A survey of 100 sequenced H. pylori genomes showed that the ApbC sequence is highly conserved in H. pylori (98.37–100% identity).…”
Section: Resultsmentioning
confidence: 98%
“…Analysis of the amino-acid sequence of H. pylori HP0207 suggests the protein belongs to the Nbp35/ApbC family, a well-studied class of proteins with ATPase activity, known to bind and transfer Fe–S clusters in vitro as well as in vivo, as shown in bacteria ( Salmonella enterica serovar Typhimurium ApbC) 35 , 36 , archaea ( Methanococcus maripaludis MMP0704) 37 , 38 and eukarya ( Sacharomyces cerevisiae Cfd1 and Nbd35) 39 , 40 . A sequence alignment of HP0207 and S. Typhimurium ApbC is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) The RMSD difference in welldefined region between the Riemannian structures and CYANA structures; (b) the accumulative distributions of the RMSD in well-defined region for Riemannian structures and CYANA structures; (c) the RMSD difference in all region between the Riemannian structures and CYANA structures; (d) the accumulative distributions of the RMSD in all region for Riemannian structures and CYANA structures. Reprinted from ref [56]. with permission.…”
mentioning
confidence: 99%